Analysis of the Physical Condition and Skills of Persipura Jayapura’s Goalkeepers - Arsyad, Adzib Alhakim; Anwar, ⁠Saiful; Pratama, Leo; Putro , Waskito Aji Suryo; Harmaman , Harmaman; Bumburo , Bandung; Sahidi, Sahidi (Jurnal Ilmu Keolahragaan, 2026)
Background Physical condition is a fundamental factor that influences the performance and skills of soccer players, particularly goalkeepers, whose position demands optimal speed, agility, and endurance. However, the lack of empirical data on the physical condition and skill profiles of goalkeepers at the professional club level remains a challenge in developing evidence-based training programs. Objectives This study aims to analyze the physical condition and skills of Persipura Jayapura’s goalkeepers and to provide a comprehensive overview of their physical ability levels as a basis for evaluating the athletes’ performance. Methods This study employed a descriptive quantitative approach using a survey method that involved testing and measuring five goalkeepers as the total sample. Data were collected using the 50-meter run (speed), the Illinois Agility Run Test (agility), and the multistage fitness test (endurance), and were analyzed using descriptive statistics in the form of percentages and T-scores. Results The results of the study show that most goalkeepers fall into the “good” category in all components of physical fitness, with endurance being the most dominant component. No goalkeepers were found to be in the “poor” or “very poor” categories, although there were individual variations in speed and agility. Conclusions This study confirms that good physical condition contributes to a goalkeeper’s performance readiness and provides practical implications for coaches in designing training programs based on physical assessments. Theoretically, this study enriches the body of research on the physical condition profile of goalkeepers, a topic that remains underrepresented in sports literature.